A Study of Thailand 4.0 Undergraduate Student’s Essentials - Boocha, Piya; Janyarat, Sirirat (Ratchaphruek Journal, 2022)
This research was divided into 2 phases. Phase 1 aimed to study 1) the expectations of essential skills among Thai graduates. The samples consisted of 8 entrepreneurs and university instructors. In-depth interviewing was used for collecting data. Content analysis was applied for analyzing, and 2) the needs of essential skills among Thai graduates in Thailand 4.0 era. Focus group was used for collecting data from 15 undergraduate students, and questionnaire was used to collect data from 540 undergraduate students. Content analysis and Priority Needs Index were applied. Phase 2 aimed to develop a causal model of psychosocial and behavioral factors affecting the essential skills among graduates. The samples consisted of 645 undergraduate students. The questionnaires were collected and analyzed with Structural Equation Model. The research showed that 1) the essential skills of graduates based on the expectations of instructors and entrepreneurs were critical thinking and problem-solving skills, creativity and innovation skills, lifelong learning skills, cooperation and teamwork skills, communications, information and media literacy skills; 2) the needs for the essential soft skills of graduates categorized by characteristics of skills that should be developed were creativity and innovation skills, lifelong learning skills, leadership and social influence skills, while hard skills were found in English proficiency, research, and professional skills; 3) the proposed causal relationship model fitted with the empirical data ( 2 = 9.62, df = 5, p-value= 0.09, RMSEA = 0.04, SRMR 0.01, CFI = 1.00, NFI = 1.00, GFI = 1.00)